Ride to hell's gate - Cotton, Ralph W. (New York : Signet, 2008)
"Lawrence Shaw still has the reputation as the fastest gun alive. But since the death of his beloved Rosa, his shots have come out of a bottle. Then a friend gets Shaw a job helping a widow with her ranch, and Fast Larry sees the glimmer of a second chance. Unfortunately the Barrows Brothers Gang has other plans..."--P. 4 of cover.
Keywords: Outlaws -- Fiction; Revenge -- Fiction; Widows -- Fiction; Western stories